The evolution of Titan's high-altitude aerosols under ultraviolet irradiation. (June 2018) - Carrasco, Nathalie; Tigrine, Sarah; Gavilan, Lisseth; Nahon, Laurent; Gudipati, Murthy
Abstract The Cassini–Huygens space mission revealed that Titan's thick brownish haze is initiated high in the atmosphere at an altitude of about 1, 000 km, before a slow transportation down to the surface. Close to the surface, at altitudes below 130 km, the Huygens probe provided information on the chemical composition of the haze. So far, we have not had insights into the possible photochemical evolution of the aerosols making up the haze during their descent. Here, we address this atmospheric aerosol aging process, simulating in the laboratory how solar vacuum ultraviolet irradiation affects the aerosol optical properties as probed by infrared spectroscopy. An important evolution was found that could explain the apparent contradiction between the nitrogen-poor infrared spectroscopic signature observed by Cassini below 600 km of altitude in Titan's atmosphere and a high nitrogen content as measured by the aerosol collector and pyrolyser of the Huygens probe at the surface of Titan. How does Titan's thick brownish haze chemically evolve as it is transported from the upper atmosphere observed by Cassini to the lower regions sampled by Huygens? Laboratory vacuum ultraviolet experiments may explain the observed changes in nitrogen chemistry.